SEMAR MENCARI RAGA KARYA SINDHUNATA SEBAGAI NOVEL BERDIMENSI BARU DALAM GENRE SASTRA INDONESIA MODERN - B. Rahmanto (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2005)
This article discusses to of Sindhunata’s novels, Semar Mencari Raga (1996) and Tak Enteni Keplokmu Tanpa Bunga dan Telegram Duka (2000), as novels produced by a local writer (Yogyakarta) who possesses an aesthetic vision marked by the blurring of literary genres that opens up a new dimension in the creative process. Semar Mencari Raga came out of Sindhunata’s intense observation of the paintings of ten artist living in Yogyakarta (Agung Leak Kumiawan, Djoko Pekik, Eddie Haru, Hanura Hosea, Hari Budiono, Hary Wahyu, Hendro Suseno, Murtianto Antik and Suatmaji). All of them took Semar as their central theme. Meanwhile, Tak Enteni Keplokmu Tanpa Bunga dan Telegram Duka was inspred by the paintings of Djoko Pekik that depicted wild boars. Sindhunata immersed himself in each painting, attempting to understand them without making any negative judgement regarding their qualities. Equipped with his genius for apprecialion, he then played with his wild imagination, expanding the horizon of neu possibilities to give birth to a new kind of novel rich with social critique that confronted the dark side of the New Order’s authoritarian and mililaristic politicians near the end of Soehurto’s rule. Both novels are imbued with profound philosophical reflections on the Javanese culture, which is part of Sindhunata's everyday life. Kata kunci: novel, kritik sosial, dimensi baru.